The Dark Knight’s Dystopian Vision: Batman, Risk, and American National Identity - Jeanne Cortiel; Laura Oehme (European Journal of American Studies)
This essay argues that Frank Miller’s Batman: The Dark Knight Returns (1986) and Batman: The Dark Knight Strikes Again (2001-02) are grounded in a specific type of anticipatory consciousness that we read as risk consciousness. With their sustained and systematic confrontation of risk discourses, the two graphic narratives can be seen as key examples of what we call risk fiction, that is fictional engagements with and expressions of global risks that are the products of late modernity. Our focus on risk is based on Ulrich Beck’s articulation of “reflexive modernity” and reveals the specific ways in which Miller’s Dark Knight series signals a transition in American national, racial and gender identities since the 1980s. It is our contention here that Miller’s The Dark Knight Returns begins a deliberate engagement with how the sense of global risk shapes social cohesion at the height of the cold war, and The Dark Knight Strikes Again brings this engagement to the twenty-first century. We identify three levels of risk representation in the two graphic narratives: apocalyptic riskscapes, individual risk-taking as edgework, and the staging of global risk in the media.